"Bioinspired" Membrane-Coated Nanosystems in Cancer Theranostics: A Comprehensive Review - Nimeet Desai; Dhwani Rana; Shreya Pande; Sagar Salave; Jyotsnendu Giri; Derajram Benival; Nagavendra Kommineni (MDPI AG, 2023)
Achieving precise cancer theranostics necessitates the rational design of smart nanosystems that ensure high biological safety and minimize non-specific interactions with normal tissues. In this regard, "bioinspired" membrane-coated nanosystems have emerged as a promising approach, providing a versatile platform for the development of next-generation smart nanosystems. This review article presents an in-depth investigation into the potential of these nanosystems for targeted cancer theranostics, encompassing key aspects such as cell membrane sources, isolation techniques, nanoparticle core selection, approaches for coating nanoparticle cores with the cell membrane, and characterization methods. Moreover, this review underscores strategies employed to enhance the multi-functionality of these nanosystems, including lipid insertion, membrane hybridization, metabolic engineering, and genetic modification. Additionally, the applications of these bioinspired nanosystems in cancer diagnosis and therapeutics are discussed, along with the recent advances in this field. Through a comprehensive exploration of membrane-coated nanosystems, this review provides valuable insights into their potential for precise cancer theranostics.